A Rapid Design‐Led Approach to Innovation Readiness: Advantages and Challenges. Issue 1 (18th March 2019) - Gribbin, John; Spencer, Nick; Bailey, Mark
Abstract : The purpose of this article is to report on an ongoing suite of research that aims to develop a design‐led approach to help small and medium‐sized enterprises (SMEs) understand their innovation readiness. At present, a number of tools are available to organizations when carrying out an audit to determine their innovation readiness; however, none of these methodologies have been connected to the practice of design‐led innovation. This article begins to address this gap by presenting a review of a 12‐hour intervention carried out in collaboration with a fund‐management organization located in northeast England as part of a European Union–funded research and innovation program, Creative Fuse. The article utilizes a qualitative approach guided by case study principles, semi‐structured interviews, and action research to reflect on the proposed design‐led approach to assessing innovation readiness. Advantages and challenges to the approach are considered with the intention of developing a practical approach to assessing innovation readiness within SMEs, which builds on design principles in order to rapidly outline the opportunities and potential barriers facing organizations when it comes to identifying areas for future innovation.